Autobiographical reflections on what it means to experience disruption. Issue 5 (2nd September 2016) - Lindsay, Gail M; Schwind, Jasna Krmpotić; Papaconstantinou, Efrosini; Smye, Victoria; Cross, Nadine
Abstract: Accepting disruption as an inevitable occurrence in life, five nurse-teacher-researchers explore their experience with being disruptive/being disrupted. Reflection on the all-encompassing embodied experience of disruption takes us through a process of exploration and meaning-making. We pause to show what it is like to be in-between the known and unknown in creating a life in academia through stories. Plotlines such as being in-between family and work; transplanted outsider seeking a sense of belonging; going into the chaos while feeling invisible; and self-induced disruption in response to loss illuminate our reflection. The metaphor of the breathturn allows us to reconstruct our experience and to discern possibilities beyond the usual negative connotations.